2017
DOI: 10.3389/fpls.2017.00795
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Transcriptomes in Rhizophoraceae Provides Insights into the Origin and Adaptive Evolution of Mangrove Plants in Intertidal Environments

Abstract: Mangroves are woody plants that grow at the interface between land and sea in tropical and subtropical latitudes, where they exist in conditions of high salinity, extreme tides, strong winds, high temperatures, and muddy, anaerobic soils. Rhizophoraceae is a key mangrove family, with highly developed morphological and physiological adaptations to extreme conditions. It is an ideal system for the study of the origin and adaptive evolution of mangrove plants. In this study, we characterized and comprehensively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 72 publications
8
30
2
1
Order By: Relevance
“…Mangroves comprise a group of terrestrially derived coastal shoreline plants suggested to have evolved around the Tethys Sea during the late Cretaceous to Paleocene–Eocene (Ellison, Farnsworth & Merkt, ). Recently, Guo et al () reported a post‐Cretaceous–Paleogene boundary divergence of the mangrove clade from the terrestrial lineage within Rhizophoraceae. The mangrove ferns of the genus Acrostichum may have evolved and diverged from a terrestrial lineage in the late Cretaceous and are suggested to be among the oldest members of the mangrove ecosystem (Zhang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Mangroves comprise a group of terrestrially derived coastal shoreline plants suggested to have evolved around the Tethys Sea during the late Cretaceous to Paleocene–Eocene (Ellison, Farnsworth & Merkt, ). Recently, Guo et al () reported a post‐Cretaceous–Paleogene boundary divergence of the mangrove clade from the terrestrial lineage within Rhizophoraceae. The mangrove ferns of the genus Acrostichum may have evolved and diverged from a terrestrial lineage in the late Cretaceous and are suggested to be among the oldest members of the mangrove ecosystem (Zhang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The overall annotation rates for the two Cycas species studied here, C. hainanensis and C. changjiangensis , were not very high, with only about half of the unigenes annotated using the Nr (45% in C. hainanensis , 52% in C. changjiangensis ) and KOG (42% in C. hainanensis , 48% in C. changjiangensis ) databases. This may be due to the low representation of gymnosperm species in the available annotation databases (Li et al., ), although a small proportion of unannotated genes might be Cycas ‐specific genes associated with certain genus‐specific characteristics (Mao et al., ; Guo et al., ). The high level of similarity between the GO categories associated with the C. changjiangensis and C. hainanensis unigenes might suggest a conserved gene repertoire for these species, and also indicates their very recent divergence (Yang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Cycas hainanensis grows well in thick forests with high temperatures and wet substrates, whereas C. changjiangensis is mainly distributed on bare rock in arid conditions. These differences in the microhabitats of these two Cycas species suggests that natural selection may be the major force that has driven their divergence and evolution (Guo et al., ). The pattern of selective pressures across a genome may therefore be useful for making inferences about adaptive evolution (Kunstner et al., ; Siol et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…There has also been more work probing adaptation to harsh and unconventional environments including elevated mountain areas (Yang et al ., ; Jia et al ., ), inter‐tidal mangrove areas (Yang et al ., ; Guo et al ., ), and even the Antarctic (Cho et al ., ). In the case of biotic interactions, field transcriptomes have been sequenced from microbial plant colonizers and the plant host in tandem in a dual RNA‐seq approach (Hubbard et al ., ; Kamitani et al ., ).…”
Section: From Lab To the Field: Plant Genomics And Systems Biology Imentioning
confidence: 99%